Effect of Corporate Social Responsibility on Consumer Satisfaction and Consumer Loyalty of Private Banking Companies in Peru - Leclercq-Machado,Luigi (2022)
“This study aimed to determine the effect of corporate social responsibility (CSR) on consumer satisfaction and loyalty in the Peruvian private banking sector. A total of 390 bank consumers fulfilled an online survey. It evaluated the effect of corporate social responsibility (CSR), customer satisfaction (CS), and customer trust (CT) on customer loyalty. The results suggest that CSR and customer satisfaction, through customer trust, have a positive effect on customer loyalty. The model explained 63.6% of customer loyalty. Outcomes of the bootstrapping test showed that the path coefficients were significant. The research findings may help bank managers to understand customers’ satisfaction and trust, which can create a preference and loyalty for their firms. The study’s novelty is based on the use of the partial least square structural equation modeling technique (PLS-SEM) to evaluate CSR in the financial sector in Peru. “